Reassessing the grammar-translation method in modern language pedagogy - Yuldashova, Nargiza (The Lingua Spectrum, 2025)
This article revisits the Grammar-Translation Method (GTM) in the context of contemporary language teaching approaches. It begins by providing a historical overview of GTM, tracing its evolution and initial widespread use in language education. The article then delves into the core features of the method, such as its focus on grammar rules, translation exercises, and the memorization of vocabulary, which were designed to build linguistic accuracy. The study critically examines the relevance of GTM in today’s language classrooms, particularly in environments that prioritize communication and student-centered learning. By comparing GTM with modern, communicative teaching methods, the research highlights both its pedagogical advantages, such as promoting grammatical precision and translation skills, and its limitations, including its lack of focus on real-life language use. The paper concludes with a discussion on how GTM, despite its drawbacks, can still be effectively integrated in certain contexts to complement more interactive, communicative strategies in language instruction.